ANALISIS PENGARUH BEBAN PAJAK TANGGUHAN TERHADAP LABA BERSIH PADA PERUSAHAAN TRANSPORTASI DAN LOGISTIK YANG TERDAFTAR DI BEI PERIODE TAHUN 2022-2023 - Sabrina, Diffa Putri; Putri, Fadilla Rafida; Madyastuti, Satya Vira; Krisyanto, Vella Angellia Wahyu (Jurnal Ilmiah Cendekia Akuntansi; Vol 9 No 3 (2024): JuliDO - 10.32503/cendekiaakuntansi.v9i3.5562, 2024)
This research aims to analyze the effect of deferred tax burden on the net profit of transportation and logistics companies listed on the Indonesia Stock Exchange (BEI) in 2022 to 2023. Deferred tax expense is the amount of tax recognized for temporary differences between taxable income and accounting profit. This research used purposive sampling to select 27 companies from a population of 37 transportation and logistics companies listed on the IDX. The data used are annual financial reports audited by independent auditors. Data analysis was carried out using logistic regression using Microsoft Excel 2007 and SPSS 25 software. Research findings show that deferred tax expenses have a significant influence on a company's net profit. This insight is important for investors and business managers to understand how deferred tax expenses impact earnings management.